PENGARUH PERILAKU PIMPINAN, DISIPLIN KERJA, DAN GAJI TERHADAP KINERJA KARYAWAN PADA DEPARTEMEN PRODUKSI PT. GEMBIRA BATAM - Dewi Permatasari; Hendri Herman (LPPM Universitas Ibnu Sina, 2022)
The purpose of this study was to determine: (1) To determine the effect of leadership behavior on employee performance at PT. Gembira Batam. (2) To determine the effect of work discipline on employee performance at PT. Gembira Batam. (3) To determine the effect of salary on employee performance at PT. Gembira Batam. (4) To determine the effect of leadership behavior, work discipline and salary simultaneously affecting employee performance at PT. Gembira Batam. The dependent variable of this study is employee performance (Y). The independent variables include: leadership behavior (X1), work discipline (X2), and salary (X3). The research method used is quantitative research methods. The sampling technique used purposive sampling method with a total sample of 67 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression, t test, F test, and R2. The results of this study indicate that: (1). There is an influence of leadership behavior on employee performance at PT. Gembira Batam is evidenced by the t value of 2.478 with a significant value of 0.000 <0.05 and a regression coefficient of 0.023, (2). There is an effect of work discipline on employee performance at PT. Gembira Batam is evidenced by the t value of 5.794 with a significant value of 0.000 <0.05 and a regression coefficient of 0.392, (3). There is an effect of salary on employee performance at PT. Gembira Batam is evidenced by the t value of 9.973 with a significant value of 0.000 <0.05 and a regression coefficient of 0.584, and (4). There is an influence of leadership behavior (X1), work discipline (X2), and salary (X3) simultaneously. on employee performance at PT. Gembira Batam. evidenced by the calculated F value of 58.027 with a significant value of 0.000 <0.05.